THE EFFECTS OF BRAND EXPERIENCE ON BRAND LOYALTY MEDIATED BY BRAND PASSION, SELF-BRAND CONNECTION, BRAND AFFECTION, AND CUSTOMER SATISFACTION ON SMARTPHONE USERS IN INDONESIA - Revaldi, Aditya; Kurniawati, Kurniawati; Hayuningtyas, Latifianisa; Suhardi, Putri Kusumastuti; Gantini, Atikah (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
This study examines the impact of brand experience on brand loyalty with the mediation effect of brand passion, self-brand connection, brand affection, and customer satisfaction of smartphone users in Indonesia. This study used a sample of 259 respondents who have been using smartphones for at least two years. The data was obtained using purposive sampling by filling out an online questionnaire. Data analysis generated by Structural Equation Modeling (SEM). The results of this study show that brand experience has little impact on brand loyalty. However, brand experience has a positive influence on brand loyalty if it is mediated by brand passion, self-brand connection, brand affection, and customer satisfaction. The implication of this study argues that it is better for companies engaged in the smartphone industries can pay attention to the role of brand passion, self-brand connection, brand affection, and customer satisfaction as factors that can mediate brand experience to increase the tendency of brand loyalty. Companies should enhance the focus, not only on the visual and feature but also the emotional indicators so that the customer could have a good experience to become a loyal one.JEL: M30, M31, M39.